Yarrowia lipolytica as an emerging biotechnological chassis for functional sugars biosynthesis. Issue 4 (21st February 2021) - Bilal, Muhammad; Xu, Shuo; Iqbal, Hafiz M. N.; Cheng, Hairong
Abstract: Functional sugars have unique structural and physiological characteristics with applied perspectives for modern biomedical and biotechnological sectors, such as biomedicine, pharmaceutical, cosmeceuticals, green chemistry, and agro-food. They can also be used as starting matrices to produce biologically active metabolites of interests. Though numerous chemical synthesis routes have been proposed and deployed for the synthesis of rare sugars, however, many of them are limited and economically incompetent because of expensive raw starting feedstocks. Whereas, the biosynthesis by enzymatic means are often associated with high catalyst costs and low space-time yields. Microbial production of rare sugars via green routes using bio-renewable resources offers noteworthy solutions to overcome the aforementioned limitations of synthetic and enzymatic synthesis routes. From the microbial-based synthesis perspective, the lipogenic yeast Yarrowia lipolytica is rapidly evolving as the most prevalent and unique "non-model organism" in the bio-production arena. Due to high flux tendency through the tri-carboxylic acid cycle intermediates and precursors such as acetyl-CoA and malonyl-CoA, this yeast has been widely investigated to meet the increasing demand of industrially relevant fine chemicals, including functional sugars. Incredible interest in Y. lipolytica originates from its robust tolerance to unstable pH, salt levels, and organic compounds, which subsequently enable easy bioprocess optimization. Meaningfully, GRAS (generally recognized as safe) status creates Y. lipolytica as an attractive and environmentally friendly microbial host for the manufacturing of nutraceuticals, fermented food, and dietary supplements. In this review, we highlight the recent and state-of-the-art research progress on Y. lipolytica as a host to synthesize bio-based compounds of interest beyond the realm of well-known fatty acid production. The unique physicochemical properties, biotechnological applications, and biosynthesis of an array of value-added functional sugars including erythritol, threitol, fructooligosaccharides, galactooligosaccharides, isomalto-oligosaccharides, isomaltulose, trehalose, erythrulose, xylitol, and mannitol using sustainable carbon sources are thoroughly vetted. Finally, we conclude with perspectives that would be helpful to engineer Y. lipolytica in greening the twenty-first century biomedical and biotechnological sectors of the modern world.